2002
DOI: 10.1021/jp020998f
|View full text |Cite
|
Sign up to set email alerts
|

Photodissociation of Acetaldehyde, CH3CHO → CH4 + CO:  Direct ab Initio Dynamics Study

Abstract: A total of 100 trajectories for the photodissociation, CH3CHO → CH4 + CO, on the S0 potential surface have been calculated using the direct ab initio molecular dynamics method at the RMP2(full)/cc-pVDZ level of theory. The energy distributions for the relative translational energy, the CO internal energy, and the CH4 internal energy were calculated to be 28, 20, and 51%, respectively. It was predicted that the product CO is highly rotationally excited but vibrationally almost not excited; on average, the rotat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 48 publications
3
34
0
Order By: Relevance
“…However, the internal energy of the CH 4 is most highly populated with Ϸ52% of the available energy. Finally, the v-J vector correlation was also reported from the quasiclassical trajectory calculations (9), which showed almost perfect vЌJ alignment for dissociation via the 3-center TS.…”
Section: Discussionmentioning
confidence: 83%
“…However, the internal energy of the CH 4 is most highly populated with Ϸ52% of the available energy. Finally, the v-J vector correlation was also reported from the quasiclassical trajectory calculations (9), which showed almost perfect vЌJ alignment for dissociation via the 3-center TS.…”
Section: Discussionmentioning
confidence: 83%
“…Acetaldehyde ͑CH 3 CHO͒ photodissociation has been the subject of considerable interest for many years both from the experimental 1-20 and theoretical [21][22][23][24][25][26][27][28][29][30][31][32][33][34] points of view. In fact, this molecule is a key case in the field of reaction dynamics, representing a beautiful example where theoretical work has played a fundamental role in the explanation of the vast experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…1͒, the geometry of which has been determined by ab initio calculations. 11,25,26,28 The theoretical data available at that time were enough to describe the main experimental findings: a relatively large kinetic energy release due to the steep down slope on the PES once the TS ‫ء‬ is surmounted, a large rotational excitation and no vibrational excitation in CO, and vibrationally hot CH 4 . However, in 2006, Houston and Kable 14 described the existence of another type of CO fragments after the photodissociation of acetaldehyde at 308 nm.…”
Section: Introductionmentioning
confidence: 99%
“…12 Trajectory calculations initiated at the S0 TS leads to rotationally excited CO products and partitioning of a large fraction of the available energy into translational recoil, in agreement qualitative with the experimental 5 observations. 13,14 Acetaldehyde was the second molecule to show evidence of photochemical roaming, with the observation of low-J CO formed in conjunction with highly internally excited CH4, [15][16][17][18] consistent with the dynamical signatures established for roaming in formaldehyde. [19][20][21] Quasiclassical trajectory calculations on ab initio potential surfaces supported this interpretation and indicated that roaming involved frustrated dissociation and subsequent intramolecular reaction between the CH3 + HCO radical products.…”
Section: Introductionmentioning
confidence: 52%